Can you work this out?

The answer fit be 12 sef without BODMAS *side eyes*

## Thursday, November 24, 2016

#### 48 comments:

Disclaimer: Comments And Opinions On Any Part Of This Website Are Opinions Of The Writers Or Anonymous Persons And They Do Not Represent The Opinions Of StellaDimokoKorkus.com

Pictures and culled stories posted on this site will be given due credit and is not the fault of StellaDimokoKorkus.com if website culled from misrepresents source of story.

If you have a complaint or a story,Please Contact StellaDimokoKorkus.com Via

Sdimokokorkus@gmail.com

Mobile Phone +4915210329280

Subscribe to:
Post Comments (Atom)

Nah, mathematics has never been my thing. I'll pass, thank you.

ReplyDeleteI'm scared of figures, except money figures. Hehehe

3.

DeleteA=36

B=12

0 but I know say i fail am

Delete2A = (48-B)+(24+B)

Delete= 48+24-B+B

2A = 72

A = 72÷2 = 36

Apply to either equation

If A = 36; then 36 + B = 48

B = 48-36 =12

Therefore

A÷B = 36÷12 = 3

Wats all these u guys r calculating? A+B=48 and A-B=24

DeleteIf we take subtract 24 from 48 we are lef with 24 which makes A=24 as well as B. Now, A÷B=24÷24=1

Therefore d answer is 1 joor!

Anon 4:05, if A is 24 and B is 24 that means A-B is 0 already. Nothing to divide anymore.

DeleteStop confusing yourself. Bye

0

ReplyDeletethe answer is 3.

ReplyDeleteA=36

B=12

Yeah....correct

Deleteππ

Delete24

ReplyDelete69 only the wise ones will understand. ....π

ReplyDeleteEnter your comment...ans is 3

ReplyDeleteAbeg i dont know maths. Let me wait for ogbonge people with the answer.

ReplyDeleteIts easy, follow this steps

Delete* re write any of the equation to have a 3rd equation.

*from equation 1, I can say A=48-B

*since you wrote from eqn 1, rewrite into eqn 2

A-B = 24

(48-B)-B = 24

48-2B = 24

48-24 = 2B

24 = 2B

B= 24/2

B=12

Since B is 12

A = 48 -B

A= 48-12

A=36

Therefore

A÷B = ?

36÷12=3

Answer =3

The answer na 1. Says Mrs Joan

ReplyDeleteThe answer is 1 one

ReplyDeleteA is 36

ReplyDeleteB is 12

Then A/B is= 3

A is 36

ReplyDeleteB is 12

Then A/B is= 3

a÷b=3

ReplyDeleteA = 36

ReplyDeleteB = 12

A/B = 3

3

ReplyDeleteisiro

ReplyDeleteA+B=48.......1

A=48 -B

A-B=24-----2

FROM (2): 48-B-B=24

2B=48-24

2B=24 ,THEREFORE B=12

EQUATION 1

A+B=48 ,BIS 12 SUBSITUTION A+12=48 ;A=48-12 =36

A/B=36/12 =3

Send my trophy

By their calculations u shall knw them....nice one mathematician

DeleteBingo! Thumbs up.

Deleteisiro

ReplyDeleteA+B=48.......1

A=48 -B

A-B=24-----2

FROM (2): 48-B-B=24

2B=48-24

2B=24 ,THEREFORE B=12

EQUATION 1

A+B=48 ,BIS 12 SUBSITUTION A+12=48 ;A=48-12 =36

A/B=36/12 =3

Send my trophy

isiro

ReplyDeleteA+B=48.......1

A=48 -B

A-B=24-----2

FROM (2): 48-B-B=24

2B=48-24

2B=24 ,THEREFORE B=12

EQUATION 1

A+B=48 ,BIS 12 SUBSITUTION A+12=48 ;A=48-12 =36

A/B=36/12 =3

Send my trophy

Not dey confuse person with this kind 3page solution in d name of maths.......whereas d answer na just 1 line.metcheeeeeew oversabi! Na Google help u!

DeleteJust passing by. Bye bye oo.

ReplyDeleteAnswer = 3.

ReplyDeleteA(36)+ B(12) =48

A(36)- B(12) =24

A(36)÷ B(12) = 3

Thank me later. Newest Homechick in the building.

Using simultaneous equations

ReplyDeletea+b=48 ......1

a-b=24 .......2

eqn 1 - eqn 2

=0+2b=24

b=12

Subs 12 for b in eqn 1 = a + 12 = 48 d/4 a=36

eqn 3 a/b=?,

.........36/12 =3.

+B-B eliminates each other. A+A=48+24. 2A=72. A therefore =72/2 = 36.

ReplyDeleteReplace A with 36 in the first equation to get value of B. 36 + B = 48. B =48 - 36. B = 12.

Since A = 36 and B = 12, A/B = 36/12 = 3.

Guru's in the house, hope I am correct?

I got 1

ReplyDeleteA+B=48

ReplyDeleteA-B=24

2b=24

b=12

If A+B=48

A+12=48

A=48-12

A=36

A÷B=?

36÷12=3

Answer is 3

Nope. +B-B can never give 2B

DeleteMiss blackie...thats bcos i used a minus sign

DeleteB+(-)B will give u 2b..i was eliminating A

If i used a plus sign..i would have eliminated B..

Hope you get?

Enter your comment...3

ReplyDeleteA + B = 48

ReplyDeleteA - B = 24

--------------

2A = 72

A = 36

So

A + B = 48

36 + B = 48

therefore, B = 48-36 = 12

CHECK:

A + B = 48? == 32 + 16 = 48 check

A - B = 12? ==32 - 16 = 24 check

Therefore,

A/B = 36/12 = 3 Answer

Typo

DeleteA-B = 24

36-12 = 24. I just realized the mistake. But the answer remains same

Ans = 3

A+B=48

ReplyDeletethus A=48~B

subsisting into equation 2

48-B-B=24

48-2B=24

48-24=2B

24=2B

B=12

thus A=48-12=36

A/B=36/12=3

This comment has been removed by the author.

ReplyDeleteThis comment has been removed by the author.

ReplyDeleteStella you be olodo o

ReplyDeletethe answer is 3.

Hmmmm..... Brilliant people are in this blog o. Una well done

ReplyDeleteI can only calculate it when it involves money,ejoor.

ReplyDeleteI don't know jack

ReplyDeleteA+B=48 A-B=24 A÷B=? A=36, B=12. 36+12=48, 36-12=24, then 36÷12= 3. Therefore the answer is 3.

ReplyDeleteIf you solve simultaenously, A= 36 and B=12. So 36÷12=3 ans.

ReplyDeleteSimple Math